Transcriptomic and metabonomic profiling unveils the mechanism of Tartary buckwheat and kiwi co-fermentation products in hyperlipidemia treatment - Guohui, Nan; Tingna, Xie; Qinghui, He; Hongchun, Yu; Jing, Peng; Shiyin, Jiang; Li, Li; Huawei, Yuan; Daijing, Wei; Qi, Wu (Frontiers in Pharmacology, 2025)
IntroductionTartary buckwheat (Fagopyrum tataricum, TB), a flavonoid-rich plant limited by anti-nutritional metabolites.MethodsTB was co-fermented with kiwi juice (TB-KW) through alcohol fermentation to improve flavonoid extraction and utilization. The flavonoid profile of TB-KW was analyzed through untargeted metabolomics. The anti-hyperlipidemic effects of TB-KW were assessed in zebrafish maintained on a high-fat diet through transcriptomics and metabolomics.ResultsUntargeted metabolomic analysis showed that flavonoids originating from TB, including quercetin, luteolin, quercitrin, rutin, and kaempferide, were significantly enriched in TB-KW. The data further showed that TB-KW significantly reduced lipid accumulation in zebrafish. Metabolomic profiling revealed 24 core differential metabolites (DEMs), spanning glycerophospholipids, sphingolipids, glycerolipids, and fatty acyls. Transcriptome analysis showed that TB-KW significantly regulated genes such as PLTP, ApoC1, SOAT2, SCARB1, PLA2G12B, and HMGCRa.DiscussionThese genes are associated with cholesterol metabolism and pathways linked to fat digestion and absorption, and they show a particular capacity to increase HDL synthesis. This study suggests the potential of TB-KW in improving flavonoid bioavailability and in the prevention and treatment of hyperlipidemia.